Angelica polysaccharide moderates hypoxia-evoked apoptosis and autophagy in rat neural stem cells by downregulation of BNIP3 - Yongzhen Xue; Dongmei Li; Yige Zhang; Hang Gao; Hui Li (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Neonatal hypoxia–ischemia is a troublesome disease. Angelica polysaccharide (AP) is proved to have antioxidant effects. Our study was performed to confirm the effects of AP in hypoxia-exposed neural stem cells (NSCs). NSCs were pre-treated with AP and then stimulated with hypoxia. Viability of NSCs was examined by Cell Counting Kit-8 assay. Hypoxia-introduced apoptosis was observed by flow cytometry. Essential regulators of mTOR and Notch signalling pathways were examined by Western blot. mRNA expression was accessed using qRT-PCR. Bcl2/adenovirus EIB 19kD-interacting protein 3 (BNIP3) was altered by transfection. We noticed that NSCs were sensitive to hypoxia-induced apoptosis and showed decreased viability. Moreover, Beclin and light chain 3-II was upregulated while p62 was downregulated. However, AP reversed all these results. Similarly, hypoxia decreased the phosphorylation of mTOR and p70S6K and Notch1 expression while AP increased the phosphorylation of mTOR and p70S6K as well as the expression of Notch1. BNIP3 was upregulated by hypoxia while downregulated by AP. Further experiments demonstrated that overexpression of BNIP3 broken all the effects induced by AP shown in cell viability, apoptosis, autophagy and signalling pathways. Collectively, AP alleviated hypoxia-introduced NSCs damages by maintaining cell viability, blocking apoptosis and autophagy via downregulation of BNIP3 with the activation of mTOR and Notch signalling pathways.